The experiences of frontline registered professional nurses during the covid-19 pandemic in a public hospital in the uMgungundlovu Health District of Kwa-Zulu Natal, South Africa - Govender, Moganambal (Stellenbosch : Stellenbosch University, 2023)
Thesis (MNur)--Stellenbosch University, 2023.